Brand equity and brand loyalty in the internet banking context: FIMIX-PLS market segmentation - Loureiro, S. M. C.; Miranda, F. J. (Journal of Service Science and Management, 2011)
This research presents a model that integrates trust, online risks and benefits, brand awareness/associations, perceived quality and explains how they impact on brand equity and brand loyalty in the context of internet banking. The research model estimation uses the PLS approach and applies FIMIX-PLS to segment the sample. The research findings show that the main difference characterizing the two uncovered customer segments lies in the place of residence. Thus, the impact of online benefits on trust in the service provided is stronger for the first segment than for the second. For customers of the second segment, confidence in the bank’s web site information leads to a better perception of service quality and this is very important to ensure loyalty to the brand.